2019
DOI: 10.3390/antiox8080282
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sonotrode Ultrasonic-Assisted Extraction of Proanthocyanidins from Brewers’ Spent Grains

Abstract: Brewing spent grains (BSGs) are the main by-product from breweries and they are rich of proanthocyanidins, among other phenolic compounds. However, literature on these compounds in BSGs is scarce. Thus, this research focuses on the establishment of ultrasound-assisted extraction of proanthocyanidin compounds in brewing spent grains using a sonotrode. To set the sonotrode extraction up, response surface methodology (RSM) was used to study the effects of three factors, namely, solvent composition, time of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…To complete the phenolics characterization, free proanthocyanidins were selectively extracted and quantified. Although their total content was lower than that found in a recent study on BSG (Martín-García et al, 2019), the amount of monomers resulted markedly higher than that previously found, most likely because this BSG contained maize, which was reported to have a high content of these forms (up to 43 g/kg) (Chen et al, 2017). Combined bioprocessing caused a relevant degradation of the polymeric forms of proanthocyanidins, although monomeric forms did not increase, suggesting a rapid degradation after their release.…”
Section: Discussioncontrasting
confidence: 74%
“…To complete the phenolics characterization, free proanthocyanidins were selectively extracted and quantified. Although their total content was lower than that found in a recent study on BSG (Martín-García et al, 2019), the amount of monomers resulted markedly higher than that previously found, most likely because this BSG contained maize, which was reported to have a high content of these forms (up to 43 g/kg) (Chen et al, 2017). Combined bioprocessing caused a relevant degradation of the polymeric forms of proanthocyanidins, although monomeric forms did not increase, suggesting a rapid degradation after their release.…”
Section: Discussioncontrasting
confidence: 74%
“…p-CA has been reported in levels of 2 to 3 fold lower than FA [56], in close range to FA [41,59] and sometimes only traces were observed [60]. Catechin, the most common flavonoid reported in BSG, can be extracted by using organic solvents without the need of saponification, and its content is reported to be below 10 mg/g BSG dw [49,61], which are in similar levels in this study. The remaining phenolic acids (caffeic acid, 4-hydroxybenzoic acid and protocatechuic acid) were mostly reported in literature at very low levels compared to FA or p-CA [54,62].…”
Section: Uplc-ms/ms Quantification Of Bsg Free and Bound Polyphenolssupporting
confidence: 84%
“…In this context, BSG provides numerous compounds that can serve as the basis to produce functional food and feed (Bonifácio-Lopes et al 2019;Skendi et al 2018). Thus, the use of BSG as a substrate for microbial growth to produce single cell proteins, to enhance its techno-functional properties, and to increase its commercial value has been proposed (Connolly et al 2019;He et al 2019;Ibbett et al 2019;Luft et al 2019;Marson et al 2019;Martín-García et al 2019;Shen et al 2019).…”
Section: Brewers' Spent Grain In Human and Animal Dietsmentioning
confidence: 99%